EFEKTIVITAS WAKAF POLIS ASURANSI SYARIAH DALAM UPAYA MENINGKATKAN MANFAAT BAGI PEMEGANG POLIS - Dewi Riza Lisvi vahlevi (ICO EDUSHA, 2020)
Wakaf fund distribution innovations are now increasingly varied, one of which can be through sharia insurance. This wakaf model has begun to be intensively marketed by Islamic insurance institutions. This study aims to determine the effectiveness of a combination of wakaf on Islamic insurance policies. The benefits of wakaf on this sharia insurance policy can be felt directly and indirectly for policyholders. The method used in this research is descriptive qualitative method. Data obtained from in-depth interview techniques, books and literature. The results of this study indicate that insurance claims on policyholders who die will be given to the heirs in the form of death compensation funds. And in addition to these benefits, policyholders also automatically provide waqf to previously appointed institutions. Seeing this, it can be concluded that policyholders get benefits in the world and the hereafter, namely in the form of death compensation for the heirs and the afterlife investment from part of the premium funds to waqf institutions. Keywords: wakaf, heirs, insurance policy.